2019
DOI: 10.1186/s40659-019-0234-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbamylated erythropoietin on neuronal apoptosis in fetal rats during intrauterine hypoxic-ischemic encephalopathy

Abstract: Background Hypoxic-ischemic encephalopathy (HIE) is a common disease that occurs during the perinatal period. The primary cause of neonatal HIE is related to fetal intrauterine anoxia. Carbamylated erythropoietin (CEPO), a derivative of erythropoietin (EPO), does not exert any erythropoietic effect; however, the neuroprotective effects resemble those of EPO. Previous studies have shown the potential benefits of CEPO on the central nervous system. The present study aimed to investigate the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
10
0
3
Order By: Relevance
“…24,25 Bcl-2 and Bax are major regulators of apoptosis, which play a crucial role in the regulation of apoptosis in brain injury diseases, including ICH 25 and hypoxic ischemic reperfusion (I/R). 26 As a pro-apoptotic member of the Bcl-2 family, Bax translocates from the cytoplasm to the mitochondrial outer membrane, which results in caspase 3 activation. 26 When the ratio of Bcl-2/Bax is decreased, apoptosis is induced, while the opposite occurs when it is increased.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Bcl-2 and Bax are major regulators of apoptosis, which play a crucial role in the regulation of apoptosis in brain injury diseases, including ICH 25 and hypoxic ischemic reperfusion (I/R). 26 As a pro-apoptotic member of the Bcl-2 family, Bax translocates from the cytoplasm to the mitochondrial outer membrane, which results in caspase 3 activation. 26 When the ratio of Bcl-2/Bax is decreased, apoptosis is induced, while the opposite occurs when it is increased.…”
Section: Discussionmentioning
confidence: 99%
“…The literature data show that electrophoretic mobility of CEPO is similar to rhEPO when denaturing SDS-containing gels are used. 12 CEPO mobility is higher than rhEPO in native gels, which can be explained by the increase in the net electric charge of the molecule. 13 (Figure 3b).…”
Section: Cepo Synthesis and Identificationmentioning
confidence: 91%
“…This protocol was also used in other studies that showed complete conversion of EPO to CEPO (Figure 1). 7,8,12 Surprisingly, the SAR-PAGE analysis of the CEPO product showed as broad band with an apparent mass slightly lower than rhEPO (Figure 2), even though nine carbamyl moieties were supposed to be bounded to the eight lysins and N-terminus. This should slightly (by 387 Da) increase the molecular mass of rhEPO, which should not be enough to see the difference when using the gel electrophoretic technique denaturating 10% polyacrylamide gel.…”
Section: Cepo Synthesis and Identificationmentioning
confidence: 96%
“…Профилактическое введение крысам СЕРО приводит к ингибированию экспрессии про-апоптогенного белка CC3 в мозге и регулирует соотношение Bcl-2/Bax, что в конечном счете ограничивает апоптоз нейронов и характеризуется защитным эффектом на модели внутриматочной гипоксии-ишемии [45].…”
Section: модификации эритропоэтина с селективным тканезащитным эффектомunclassified
“…Как и Эпо, Epotris проникает через ГЭБ, ослабляет нейротоксические эффекты каината, однако не стимулирует эритропоэз. В литературе присутствует информация об исследованиях пептидного аналога Эпо Epopeptide-ab, представляющего собой последовательность из 17 аминокислот (AEHCSLNENITVPDTKV), соответствующую области AB-петли Эпо (последовательность аминокислот [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47], который обладает активностью, сходной с целым белком. Нейропротективный эффект Epopeptide-ab подтвержден в опытах in vivo на модели ишемического повреждения нейронов [59].…”
Section: пептидные производные эритропоэтина обладающие тканезащитныunclassified